Morphological and systematic interpretation of some Late Cretaceous (Turonian-Santonian) irregular echinoids, Kopet-Dagh Basin, NE Iran - M. Taherpour Khalil Abad (Journal of Sciences, Islamic Republic of Iran)
Abderaz Formation is one of the Upper Cretaceous formations in the Kopet-Dagh sedimentary basin. A stratigraphic section from the mentioned formation is selected for detailed systematic description with regard to echinoids. Numerous well preserved representatives of the families Mircrasteridae wright, 1857 and Echinocorythidae Lambert, 1920 are described from the Ghaleh-Zoo stratigraphic section in the Kopet-Dagh sedimentary basin, northwest of Shirvan township (NE Iran). The age of the fossil assemblage is determined as Turonian-Santonian based on four echinoid species: Micraster (Micraster) coranguinum Leske, 1778, Micraster (Micraster) cortestudinarium (Goldfuss, 1829), Echinocorys gravesi (Agassiz & Desor, 1847) and Echinocorys ex gr. scutata Leske, 1778.